PENGGUNAAN APLIKASI GIS DALAM PENYAKIT TUBERKULOSIS DI CHERAS, KUALA LUMPUR, MALAYSIA - Shamsul Azhar Shah; Md. Idris Mohd. Nor; Abdul Hadi Harman Shah; Tahir Aris (Malaysian Journal of Public Health Medicine, 2002)
Tuberculosis remains to be one of the health problems in the world and especially in Malaysia. This study which was done in Cheras, Kuala Lumpur using GIS application to identify the geographical distribution and the trend of tuberculosis from 1996 to 2000. The study also tried to observe the ability of GIS as a surveillance tool for communicable disease. The results of the study using GIS application showed a rising trend of tuberculosis in certain areas in Cheras. The tuberculosis cases were seen to be concentrated at the medium and highly populated area of Kampung Pandan, housing area of Jalan Cheras and Bandar Tun Razak. The cases were mostly within 100 to 200 meter from each other. In general, GIS application has become a new dimension in disease control and could be used in tuberculosis surveillance activity.